La arquitectura adaptable como respuesta al riesgo por crecientes súbitas en construcciones a borde de rio. (2023)
After the latent problem in Colombia of floods and sudden increases as in the department of Tolima, the question is generated of how to make floating a construction on the edge of river, in order to mitigate the multiple consequences it causes to the inhabitants of the area.